Emotional Intelligence in Teachers’ Activities - Safina, Aelita Maratovna; Arifullina, Ramilya Umyarovna; Ganieva, Albina Mavletovna; Katushenko, Olga Aleksandrovna (Journal of History Culture and Art Research, 2020)
Emotional intelligence (EQ) development is becoming a more important issue among such significant factors as competence and efficiency due to the constant and rapid social transformations, new challenges, high social norms, and setting high professional standards. The ability to control emotions and recognize them is especially important for a future teacher who faces two objectives that make a success or failure when establishing communication: developing the personal abilities that provide a basis for emotional intelligence and developing students’ emotional intelligence. A future teacher should be involved in searching for new approaches and tools for understanding and controlling emotions, as well as developing the ability to empathize. The aim of this research is to help a teacher acquires effective skills to build optimal relationships with colleagues and students. This search is also due to the need to develop the skills to exercise self-knowledge, understand the motives and goals in a professional teaching environment, to influence the emotions of other people, and to improve the leadership qualities. The article describes the results of an experiment carried out at the Faculty of Pedagogy and Psychology of Naberezhnye Chelny State Pedagogical University and at the Faculty of Psychology and Pedagogy of Nizhny Novgorod State Pedagogical University named after K. Minin in 2019. The experiment was aimed at measuring the development level of students’ emotional intelligence that affects the quality of various aspects of professional activity. The authors discuss the main criteria for assessing the level of future teachers’ emotional intelligence and give characteristics of each criterion. We have come to the conclusion that developed skills of emotional competence are of great importance to teachers and children, and to the successful social interaction. The findings of the research can be applied when working out the programs to develop emotional intelligence in order to resolve conflicts and forecast their consequences in a professional teaching environment.